2019
DOI: 10.1016/j.avsg.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Imaging for EVAR with Mobile C-arm

Abstract: Fusion imaging is feasible with a mobile C-arm in a conventional operating room and thus represents an alternative to hybrid rooms. Its clinical benefits should be evaluated in a randomized series, but our study already suggests that EVAR procedures might be facilitated with an angionavigation system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Although heterogeneous (Q=30.6, p<0.001; I 2 =80%), the forest plot shows an estimated pooled MD with a significant difference in contrast volume of −29 mL (95% CI −40.5 to −18.5, p<0.001) after image fusion compared with no image fusion. 4,6,[17][18][19]21 The results of the hospital cohort (-6 mL, 95% CI −28.3 to 16.5, p=0.67) are comparable to Hiraoka et al, 18 which had the lowest MD among the meta-analyzed studies (-13 mL, 95% CI −22.1 to −3.50, p=0.009) in standard EVAR.…”
Section: Contrast Volumesupporting
confidence: 69%
See 1 more Smart Citation
“…Although heterogeneous (Q=30.6, p<0.001; I 2 =80%), the forest plot shows an estimated pooled MD with a significant difference in contrast volume of −29 mL (95% CI −40.5 to −18.5, p<0.001) after image fusion compared with no image fusion. 4,6,[17][18][19]21 The results of the hospital cohort (-6 mL, 95% CI −28.3 to 16.5, p=0.67) are comparable to Hiraoka et al, 18 which had the lowest MD among the meta-analyzed studies (-13 mL, 95% CI −22.1 to −3.50, p=0.009) in standard EVAR.…”
Section: Contrast Volumesupporting
confidence: 69%
“…Overall, a statistically significant difference was found in fluoroscopy time between the image fusion group and control group for complex EVAR (5 studies) [6][7][8][9][10] ; however, there was no significant difference in standard EVAR (5 studies). 6,17,[19][20][21] In addition, Stangenberg et al 21 was the only study reporting a significant fluoroscopy time reduction during standard EVAR, whereas the other 4 studies reported no difference or even an increase in fluoroscopy time as can be deduced from Table 2. Figure 3A shows the pooled results for the fluoroscopy time in standard EVAR procedures, which was not different after image fusion compared to no image fusion (0 minutes, 95% CI −3.7 to 3.6, p=0.98).…”
Section: Fluoroscopy Timementioning
confidence: 96%
“…In most FI studies, a CBCT was acquired in order to register in 3D-3D fashion. There is limited published data on 2D-3D FI registration for guidance of standard EVAR with feasibility rates of up to 95.5% [9,11,[17][18][19]. In this study, the feasibility rate for registration was 100%.…”
Section: Discussionmentioning
confidence: 75%
“…For each patient, fusion imaging was employed using the EndoNaut® (Therenva, France) station for navigation and positioning of the stent graft (12). Four surgeons participated in the study (2 junior surgeons with less than 5 years of experience and 2 senior surgeons with more than 10 years of experience).…”
Section: Fusion Imaging Workflowmentioning
confidence: 99%
“…In both cases, published studies, reviewed in the recent meta-analysis of Goudeketting et al (3), have shown that such augmented reality systems are capable of reducing the X-ray exposure time and the quantity of contrast agent injected. Specifically, use of 3D image fusion in standard and complex EVAR is associated with a significant decrease in contrast use, while radiation doses, procedure times, and fluoroscopy times are reduced in most studies, although not always significantly (4,11,12).…”
Section: Introductionmentioning
confidence: 99%